2022
DOI: 10.1128/mbio.01671-22
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Cyclic Diguanylate Interfere with Beneficial Bacterial Colonization

Abstract: There is substantial interest in studying cyclic diguanylate (c-di-GMP) in pathogenic and environmental bacteria, which has led to an accepted paradigm in which high c-di-GMP levels promote biofilm formation and reduce motility. However, considerably less focus has been placed on understanding how this compound contributes to beneficial colonization.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 62 publications
5
26
0
Order By: Relevance
“…Increasing studies showed that c-di-GMP is essential for host colonization including Azoarcus sp. CIB, E. amylovora and V. fischeri (Fernandez-Llamosas et al, 2021;Isenberg et al, 2022;Kharadi et al, 2022). Our data indicate that c-di-GMP affects bacterial colonization on apple fruits via the potential receptor YdaK (Figure 12), which is consistent with that previously reported in Azoarcus sp.…”
Section: Ydak Does Not Affect the Antagonistic Activity Of B Velezens...supporting
confidence: 91%
See 1 more Smart Citation
“…Increasing studies showed that c-di-GMP is essential for host colonization including Azoarcus sp. CIB, E. amylovora and V. fischeri (Fernandez-Llamosas et al, 2021;Isenberg et al, 2022;Kharadi et al, 2022). Our data indicate that c-di-GMP affects bacterial colonization on apple fruits via the potential receptor YdaK (Figure 12), which is consistent with that previously reported in Azoarcus sp.…”
Section: Ydak Does Not Affect the Antagonistic Activity Of B Velezens...supporting
confidence: 91%
“…C-di-GMP is a nearly ubiquitous bacterial nucleotide messenger that regulates a variety of important processes, including biofilm, antibiotic production and host colonization (Xu et al, 2018;Chou et al, 2020;Fernandez-Llamosas et al, 2021;Isenberg et al, 2022;Kharadi et al, 2022). In response to external stimuli, c-di-GMP is synthesized from 2 GTP molecules by diguanylate cyclases (DGCs) characterized by GGDEF domain.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not unreasonable to imagine that although cellulose can have a positive role during the early steps of this plant–bacteria interaction, a continuous overproduction of this β-glucan over the whole infection process, e.g., through the infection thread, could have a pernicious effect for the symbiotic establishment. This seems also to be the case in other bacteria-host associations, where the overproduction of cellulose generated by high c-di-GMP intracellular levels negatively affects the production of other EPS involved in the symbiotic process [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on these results, we hypothesize that increased cyclic-di-GMP in the prophage KO strains leads to reduced motility and increased biofilm formation. Increased cyclic-di-GMP levels have also been reported to reduce motility and impact biofilm morphology in Vibrio fischeri [80]. It has also been reported that the influence of a Vibrio anguillarum prophage is repressed by specific quorum sensing mechanisms and that this action results in an increase in biofilm formation [81].…”
Section: Discussionmentioning
confidence: 99%